PORE SIZE MEASUREMENT IN SOIL: A REVIEW OF METHODOLOGY (Biological Sciences - PJSIR, 2001)
An accu rate and complete anal ys i s of pore size distri bution of a soi I is useful for i nterpreti n g structural ch an ges and for predicti ng water flow rate, water storage capacity, water ava il abili ty to pl ant and rate of diffusion of gases. Water release curve (relation shi p between soi l water content and su ction ) is widel y u sed to obtai n pore size distri buti on s bu t is not depend able i n fine-textu red soi l s that shri nk on drying. There are other methods (ni trogen sorption, m ercury i n t ru si on porosi metry, non-pol ar liqu id desorption and image anal y si s) to overcom e this probl em. In anal ysing the pore size di stribution from the methods (except image anal ysi s) genera ll y capi ll ary m odel is u sed assu mi n g the pores are cylindri cal or sl i t-shaped. Li ke water desorpti on , other method s also have disadvantage of pre-dryi ng of soil sampl es without ch anges in the pore system  along others.  Stereological  i mage  anal ysi s (of a soi l) can provid e quanti t ative  three  di m en sion al inform ation abou t i t s stru ctu ral param eters and also u sed to ident ify patterns of water and solu te move m ent. These methods of pore size measurement s are discu ssed , com pared and thei r use i n soil studies i s discussed.